Adaption strategies and Impact of Climate Change on Water Resources: A Case study of Tauni Devi Block of Hamirpur District - Kumari, Binita; K. Attri, Pawan (IJRDO-Journal of Applied Science, 2016)
A study to know the status of climate change impact on water sources was conducted in villages of Tauni Devi Block of Hamirpur district of Himachal Pradesh. The study has shown that there are number of traditional drinking water sources in this area. The main traditional sources for the drinking water in study area are wells, baories and khatries. Piped water supply had also been provided to almost every house. A survey for drinking water status was conducted during the field survey and it is enumerated that the Total of 1302 (Khandera,550;Narsin ,752) habitations are in the studied village . The piped water supply schemes are given from three different IPH division these are:Hamirpur, Bhoranj and Uhal. Water requirement and water supplied by IPH department to the above villages are Khandera; 38500 Ltrs, Narsin; 52640 Ltrs accordingly in 112+152 private tapes and 11 public tapes However IPH department take care of other source of water i.e. 9 hand pumps in two village. Source of this water supply to the Khandera village is River Beas (underground water) LWSS Logwalti Bamson and to Narsin from Infiltration gallery at Gudhwin Khad. Climate change is likely to increase the variability of water resources affecting human health and livelihoods. The projected increase in the frequency and magnitude of high intensity rainfall events could affect infiltration and groundwater recharge with further implications for water availability for people as well as water accessibility for plants. The anticipated increase in variability in availability of water because of climate change should be dealt with by increasing water storage in its various forms, namely, soil moisture, ponds, ground water, small and large reservoirs and traditional water systems must be reexamined, reinvestigated and preserved.